Challenges undertaking procedures requiring asepsis: a qualitative interview study with nurses. (March 2023) - Gould, D.J.; Courtenay, M.; Gallagher, R.; Hawker, C.; Chudleigh, J.; Purssell, E.; Drey, N.S.
Summary: Background: Invasive devices and breaches to skin and mucous membranes increase susceptibility to infection. Nurses frequently undertake procedures requiring asepsis (PRAs), but report challenges and unwarranted variations in practice. Objective: To explore nurses' experiences, perceived gaps in information and support needed to conduct PRAs. Methods: Qualitative interviews were undertaken with 20 nurses in the UK National Health Service between September 2021 and January 2022 employing approaches to sampling and data collection adopted in grounded theory. Results: Informants were employed in diverse clinical settings. They thought that outside operating theatres, attempts to maintain asepsis would inevitably be compromised, but that much could still be done to contain the risk of contaminating susceptible sites irrespective of circumstances. Suboptimal practice was reported, and informants were unclear whether asepsis was needed to perform routine procedures (e.g. dressing chronic wounds, manipulating indwelling intravascular lines). Problems were attributed to inadequacies in nursing education, poor access to continuing professional development, and carelessness of junior nurses and medical staff. Informants wanted more detailed guidelines to conduct PRAs. Senior nurses wanted procedures to be conducted in the same way regardless of circumstance. Nurses who undertook PRAs regularly suggested that guidelines should be flexible. Conclusion: There is a need for detailed guidelines to inform PRAs, better access to clinical updating, and improvements in pre-registration nursing education. To meet contemporary standards, guideline generation should adopt recognized methodology. Student nurses should be introduced to the knowledge and skills required to undertake and adjust PRAs according to circumstance during simulated practice before contact with real patients.